Development of Microstructure and Mechanical Properties of TiAl6V4 Processed by Wire and Arc Additive Manufacturing - Elitzer, Daniel; Jäger, Stefan; Höll, Clara; Baier, Daniel; Varga, Rosa; Zaeh, Michael F.; Göken, Mathias; Höppel, Heinz Werner (Advanced Engineering Materials, 2022)
Wire and arc additive manufacturing (WAAM) has the potential to significantly reduce material waste due to the milling of components made of TiAl6V4 (Ti-64). To keep up with the market development, this resource-efficient technology is becoming increasingly important to achieve climate policy goals. Therefore, this study not only focuses on the influence of different process parameters, such as torch and wire feed speed, but also different gas mixtures on the microstructure and related mechanical properties, as well as on the scalability by investigating single- to multilayer welded structures. The wire feed speed is found to have a major influence on the geometry and mechanical properties. The use of different process gases, i.e., argon (Ar), helium (He), and a mixture of 70% He and 30% Ar neither significantly affect the microstructure nor the mechanical properties. It is also found that a solution heat treatment followed by an annealing step degrades mechanical properties, while an ordinary stress-relief heat treatment leads to improved mechanical properties. It is shown that by adapting WAAM process and heat treatment parameters, mechanical properties of additively produced specimens can be achieved, which are fully comparable to milled components.
CRIS-Team Scopus Importer:2022-09-30
Keywords: additive manufacturing; alpha-beta alloys; heat treatments; mechanical properties; microstructures; Ti-64; WAAM